Practitioner Profile: Nikiya Spence - Nikiya Spence (Journal of Financial Therapy, 2018)
Nikiya Spence, LCSW is a licensed psychotherapist and Certified Money Coach with over seventeen years of clinical experience. Throughout the years, Nikiya has had an innate interest in money education and exploring the relationship that people have with money. As a therapist, it became obvious to Nikiya that although many of her clients did not specifically seek help related to their money issues, many of their problems and causes of stress were rooted in their relationship with money. In fact, their money problems often impacted their work, relationships, and families. It became apparent to Nikiya that it wasn’t the lack of money that created stress and anxiety, but how people mismanaged their finances.